2020
DOI: 10.24112/jaes.040004
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Site Selection of Solar Parks in Bangladesh: A Delphi-AHP Analysis

Abstract: The demand for electricity is increasing fast in Bangladesh to sustain rapid economic growth. The largest share of electricity in Bangladesh is produced by fossil fuel powered electricity generation plants. Though solar energy has high potential in Bangladesh due to favorable geographical location, very little initiative has been taken to develop the solar energy sector. At present, the Bangladesh government’s approval criteria for site selection of solar energy parks does not have any scientific basis. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In the second step, the experts are asked to respond to the question set to identify criteria weightage. The following criteria were initially picked for the first round of the questionnaire based on a literature study 33,37–40 . These criteria are very effective for the installation of the solar plant to get the maximum output from the plant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second step, the experts are asked to respond to the question set to identify criteria weightage. The following criteria were initially picked for the first round of the questionnaire based on a literature study 33,37–40 . These criteria are very effective for the installation of the solar plant to get the maximum output from the plant.…”
Section: Methodsmentioning
confidence: 99%
“…21,28,29,31,32 Studies revealed that very low works on site selection for solar plants have been accomplished in Bangladesh. Rahman et al 33 have presented a delphi-AHP analysis framework to select criteria for solar park in Bangladesh, but no suitable site is proposed for solar park. Ali et al 34 proposed a hybrid multi-criteria decision-making method to identify the best renewable energy technology for Rohingya refugees in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and quantitative distribution of incoming solar radiation also depends on aspect and latitude of the region. Additionally, it has been investigated that high latitude has higher solar irradiation thus taking it into account can be a prudent decision when establishing a substantial PV plant (Rahman et al 2020;Raja 1994). Considering the stability of foundation, ease of construction and simplicity of photovoltaic panels installation, regions having steep slopes are generally avoided.…”
Section: Criteria For Solar Plant Site Selectionmentioning
confidence: 99%
“…Several works have been done regarding conventional solar energy in Bangladesh, a few of them are solar home system, solar pump/irrigation systems, and solar parks (Amin et al, 2014;Chowdhury et al, 2011;Hossain et al, 2015;Islam et al, 2017;Liza and Islam, 2020;Najmul Hoque and Das, 2013;Rahman et al, 2020). However, there have been a few studies on marine vessels (Atkinson, 2016;Kapus ćik et al, 2019;Kobougias et al, 2013;Nasirudin et al, 2017;Spagnolo et al, 2012;Verma and Kumar, 2021;Winebrake et al, 2007) that all looked at traditional stand-alone solar PV worldwide, but anyone does not work on design regarding "flower-shaped solar PV tower," shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%